What happened in history - Childe,Gordon.V (NewDelhi : Aakar, 2022)
In this book the author discusses the changes in material well being and mental outlook which have taken place throughout the ages up to the break up of the Roman empire.He gives us brief survey of what he describes as Palacolithic and Mesolithic savagery of Neolithic barbarism of the rise of the Metal Age culture and so on untile a climax was reached as a result of the Old World unity made possible by the expolite of Alexander the Great.Finally there is stimulating chapter with the author's views about the decline and fall of the ancient world.
1.archaeology and history, 2.palaeolithic savagery, 3.neolithic barbarism, 4.the higher barbarism of the copper age, 5.the urban revolution in mesopotamia ,6. early bronze age civilization in egypt, 7.the expansion of civilization ,8.the culmination of bronze age civilization, 9.the early iron age, 10. government religion and science in the iron age , 11.the climax of ancient civilization , 12.the decline and fall of the ancient world.
Includes index.
Keywords: History; Civilization ancient